A METHOD OF SOLVING ACCOUNTING PROBLEMS. - Goggin, W. J. (The Accounting Review, 1926)
Accounting instructors at quiz and examination periods are placed on their mettle to prepare questions and problems, which may be answered by a student, who naturally works very slowly, within the time limit set for examinations. How many times we find the complaint that the quiz or examination is too long Certified Public Accountant (CPA) candidates likewise continually criticize the CPA examination questions as being too long. If students and candidates taking examinations were familiar with a satisfactory short method of solving problems, their chances of completing the work within the time limit described would in many cases be greatly increased. And examiners should be glad to encourage the use of such a method, assuming that it will serve to bring out all the essential features of the problems set. A question has been often raised by students as to the acceptability of this type of working papers by examiners. There is no doubt of the working papers being acceptable if the results and technique are correct.